A study of deformation and strain induced in bulk by the oxide layers formation on a Fe-Cr-Al alloy in high-temperature liquid Pb-Bi eutectic. (1st June 2018) - Popovic, M.P.; Chen, K.; Shen, H.; Stan, C.V.; Olmsted, D.L.; Tamura, N.; Asta, M.; Abad, M.D.; Hosemann, P.
Abstract: At elevated temperatures, heavy liquid metals and their alloys are known to create a highly corrosive environment that causes irreversible degradation of most iron-based materials. It has been found that an appropriate concentration of oxygen in the liquid alloy can significantly reduce this issue by creating a passivating oxide scale that controls diffusion, especially if Al is present in Fe-based materials (by Al-oxide formation). However, the increase of the temperature and of oxygen content in liquid phase leads to the increase of oxygen diffusion into bulk, and to promotion of the internal Al oxidation. This can cause a strain in bulk near the oxide layer, due either to mismatch between the thermal expansion coefficients of the oxides and bulk material, or to misfit of the crystal lattices (bulk vs. oxides). This work investigates the strain induced into proximal bulk of a Fe-Cr-Al alloy by oxide layers formation in liquid lead-bismuth eutectic utilizing synchrotron X-ray Laue microdiffraction. It is found that internal oxidation is the most likely cause for the strain in the metal rather than thermal expansion mismatch as a two-layer problem. Graphical abstract: Image 1 Compressive (top) and tensile (bottom) principal strain distribution in the μXRD-analyzed ferritic Fe-Cr-Al alloy material, in the bulk next to the alloy/oxide interface (arrows denote projections of the principal strain axes on X-Y plane).